Online Petitions as Part of the Right to Freedom of Expression and Its Implications for the Implementation of Government in Indonesia - Jalaluddin Jalaluddin; Sa'adah Sa'adah; Nur Zaqia (Kosmik Hukum, 2023)
This study aims to understand how the existence of the right to freedom of expression through online petitions and its implications for governance in Indonesia. This research also offers a strategy for setting petitions into laws and regulations to ensure the distribution of the people's right to freedom of expression. This normative legal research analyzes primary legal materials in the form of the 1945 Constitution and the laws and regulations under it as well as legal materials from 2018-2021 related to community activities conducting online petitions. The approaches used are the statutory approach, the concept approach, and the comparative approach. The results of the study show First, the existence of online petitions in Indonesia in 2018-2021 related to the formation of laws, namely petitions rejecting the Draft Criminal Code, Revision of the KPK Law, the Draft Job Creation Law, the Revision of the MD3 Law, the Land Law Draft, and the Music Law Draft. Second, four of the six online petitions studied were found to be successful or have ultimate implications for governance because they are able to encourage policy change. Third, as a strategy so that petitions can be responded to by the government in a mandatory manner, Indonesia needs to make laws and regulations regarding online petitions. Penelitian ini bertujuan memahami bagaimana keberadaan hak kebebasan berpendapat melalui petisi online dan implikasinya terhadap penyelenggaraan pemerintahan di Indonesia. Penelitian ini juga menawarkan strategi pengaturan petisi ke dalam peraturan perundang-undangan untuk menjamin tersalurkannya hak kebebasan berpendapat masyarakat. Penelitian hukum normatif ini menganalisis bahan hukum primer berupa UUD 1945 dan peraturan perundang-undangan di bawahnya juga bahan bahan hukum dari tahun 2018-2021 terkait dengan aktivitas masyarakat melakukan petisi online. Adapun pendekatan yang diggunakan adalah pendekatan undang-undang, pendekatan konsep, dan pendekatan komparatif. Hasil penelitian menunjukan Pertama, keberadaan petisi online di Indonesia pada tahun 2018-2021 terkait dengan pembentukan undang-undang yaitu petisi tolak Rancangan KUHP, Revisi UU KPK, Rancangan UU Cipta Kerja, Revisi UU MD3, Rancangan UU Pertanahan, dan Rancangan UU Permusikan. Kedua, empat dari enam petisi online yang diteliti dinyatakan berhasil atau berimplikasi secara ultimate terhadap penyelenggaraan pemerintahan karena mampu mendorong perubahan kebijakan. Ketiga, sebagai strategi agar petisi dapat ditanggapi pemerintah secara wajib maka Indonesia perlu membuat peraturan perundang-undangan tentang petisi online.